Proprioception: a new look at an old concept - Héroux, M. E.; Butler, A. A.; Robertson, L. S.; Fisher, G.; Gandevia, S. C. (Journal of Applied Physiology, 2022)
Proprioception, which can be defined as the awareness of the mechanical and spatial state of the body and its musculoskeletal parts, is critical to motor actions and contributes to our sense of body ownership. To date, clinical proprioceptive tests have focused on a person`s ability to detect, discriminate, or match limb positions or movements, and reveal that the strength of the relationship between deficits in proprioception and physical function varies widely. Unfortunately, these tests fail to assess higher-level proprioceptive abilities. In this Perspective, we propose that to understand fully the link between proprioception and function, we need to look beyond traditional clinical tests of proprioception. Specifically, we present a novel framework for human proprioception assessment that is divided into two categories: low-level and high-level proprioceptive judgments. Low-level judgments are those made in a single frame of reference and are the types of judgments made in traditional proprioceptive tests (i.e., detect, discriminate or match). High-level proprioceptive abilities involve proprioceptive judgments made in a different frame of reference. For example, when a person indicates where their hand is located in space. This framework acknowledges that proprioception is complex and multifaceted and that tests of proprioception should not be viewed as interchangeable, but rather as complimentary. Crucially, it provides structure to the way researchers and clinicians can approach proprioception and its assessment. We hope this Perspective serves as the catalyst for discussion and new lines of investigation.